A comparative first principles study of quantum well states in MgO barrier MTJs for STT-RAMs. (November 2020) - Yadav, Manoj Kumar; Gupta, Santosh Kumar
Abstract: This paper presents a comparative first principle study of tunneling magneto resistance (TMR), spin transfer torque (STT) and resistance area (RA) product of magnetic tunnel junctions (MTJ) having different quantum well states in middle of MgO barrier region. We report that such MTJs show enhanced STT and low RA product as compared to only MgO barrier MTJ with maintaining high TMR. Electronic structure of quantum well states adjudicates magnitude of TMR in MTJs. It is found that quantum well states having s -like character allow the transmission of Δ1 symmetry of Bloch wave whereas d -like character supports to the transmission of Δ2, Δ2′, and Δ5 symmetry. This increases transmission of spin polarized tunneling current with good spin filtering injection efficiency resulting in higher STT. It will produce less heat on applying critical switching current density ( J co ), for current induced magnetization reversal by STT phenomenon without breakdown of the barrier. Highlights: Quantum well states formed in middle of barrier region due embedding metallic layer of magnetic tunnel junction improve spin transfer torque. It reduces resistance area product maintaining good TMR compared to without quantum well states in barrier. These MTJs can be easily integrated with MOSFETs.